2023
DOI: 10.1519/jpt.0000000000000379
|View full text |Cite
|
Sign up to set email alerts
|

High Sarcopenia Awareness Contrasts a Lack of Clinical Implementation Among Geriatric Rehabilitation Health Care Professionals in the Netherlands: EMPOWER-GR

Abstract: strength (and low physical performance), and 73.8% identified sarcopenia as very important in the management of older adults admitted for rehabilitation. Although 26.2% and 18.9% of the participants reported screening and diagnosing sarcopenia, respectively, in their current practice, only 3.0% adequately used the (revised) definition of the European Working Group on Sarcopenia in Older People. When sarcopenia has been diagnosed, 65.0% reported initiating treatment consisting of resistance exercise training (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…A study using Google Trends showed that sarcopenia is poorly searched compared with osteoporosis 14 and that knowledge of osteoporosis is estimated to be over 80% among young women, which is much higher compared with the present study. 28 Similarly, the majority of healthcare professionals reports lacking knowledge to diagnose and treat sarcopenia, 12 while 83% of physicians felt competent in managing osteoporosis. 29 The age at which inpatients thought muscle mass to start to decline was higher compared with community-dwelling older adults (46 years old), while the decline may begin as early as age 30 years.…”
Section: Sarcopenia Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…A study using Google Trends showed that sarcopenia is poorly searched compared with osteoporosis 14 and that knowledge of osteoporosis is estimated to be over 80% among young women, which is much higher compared with the present study. 28 Similarly, the majority of healthcare professionals reports lacking knowledge to diagnose and treat sarcopenia, 12 while 83% of physicians felt competent in managing osteoporosis. 29 The age at which inpatients thought muscle mass to start to decline was higher compared with community-dwelling older adults (46 years old), while the decline may begin as early as age 30 years.…”
Section: Sarcopenia Knowledgementioning
confidence: 99%
“…11 Although the large majority of healthcare professionals reports to know the term sarcopenia, diagnosis and treatment implementation in clinical practice is lacking due to a lack of access to equipment, knowledge, time and priority. 12,13 Contrastingly, sarcopenia is largely unknown among the general public as the term is poorly searched on Google compared with other age-related diseases like dementia and osteoporosis. 14 Also, a majority of community-dwelling older adults lack knowledge on sarcopenia; common barriers to treatment include time constraints, costs and dislike to visiting a healthcare professional.…”
Section: Introductionmentioning
confidence: 99%